THE INFLUENCE OF LEADERSHIP STYLE, WORK ETHIC, ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON THE PERFORMANCE OF EMPLOYEES PT. LAMAN MINING - Friska Sihombing, Elisabet; Satriawan, Bambang; Indrayani, Indrayani; Khaddafi, Muammar; Ngaliman, Ngaliman (CV. Radja Publika, 2022)
The purpose of this research is to find out the influence of Leadership Style, Work Ethic, Organizational Culture and Job Satisfaction on Employee Performance of PT. Laman Mining. The subject of this study was an employee of PT. Laman mining of the sample to be taken is determined by the Slovin formula. The number of Employees of Laman Mining is 50 people. By using slovin formula with a margin of error of 5% obtained results with a presentation rate of 95%. The data was obtained by questionnaire system using likert scale. The results of this study show that leadership style, work ethic, organizational culture and job satisfaction have a positive effect on the performance of employees PT. Laman Mining. (4) The direct influence of Leadership Style (X1) on Employee Performance (Y) has a parameter coefficient of -0.165 (negative), so there is a negative influence where the more Authoritarian The Leadership Style (X1) the lower the Employee Performance (Y) and the Value P Award (X1)) on Employee Performance (Y) is -0.196> 0.05 so that it can be said that the influence of Awards on Employee Performance is insignificant. (4) The magnitude of the influence of Leadership Style (X1), Work Ethic (X2), Organizational Culture (X3) and Job Satisfaction (X4) on Employee Performance (Y) is determined by r² value, r² value on job satisfaction (Y) is 0.984 which means the influence of Leadership Style (X1)), Work Ethic (X2), Organizational Culture (X3) and Job Satisfaction (X4) on Employee Performance (Y) is 98.4%. then there is a negative influence where the more Authoritarian Leadership Style (X1) the lower the Employee Performance (Y) and P value Reward (X1) on Employee Performance (Y) is -0.196 > 0.05 so that it can be stated that the influence of Awards on Employee Performance is insignificant (4) The magnitude of the influence of Leadership Style (X1), Work Ethic (X2, Organizational Culture (X3) and Job Satisfaction (X4) on Employee Performance (Y) is determined by r² value, r² value to job satisfaction (Y) is 0.984 which means the influence of Work Motivation (X1)), Work Ethic (X2), Organizational Culture (X3)and Job Satisfaction (X4) on Employee Performance (Y) is 98.4%.